Law Enforcement in Criminal Cases Based on Restorative Justice by the Prosecutor's Office - Doris Rahmat; Santoso Budi Nursal Umar (East Asian Journal of Multidisciplinary Research, 2023)
The lack of law enforcement is trapped in legal certainty and procedural justice only in carrying out law enforcement powers, ignoring substantial justice, which is the basic goal of the law itself. The purpose of this research is to find out how law enforcement in criminal cases is based on restorative justice by the prosecutor's office. This research method uses the type of normative legal research defined as a research method on statutory rules. The nature of this research is descriptive because it describes systematically positive laws and principles or theories related to restorative justice. The results of this study show that the enforcement of criminal acts based on Restorative Justice by the prosecutor's office is carried out based on the Attorney General's Regulation of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. The public prosecutor can terminate the prosecution in the public interest.